Experimental investigation of gamma stirling engine coupling to convert thermal to cooling energy in different laboratory conditions - Sareh Daneshgar; Rahim Zahedi; Hamidreza Asemi (Global Journal of Biotechnology and Biomaterial Science - Peertechz Publications, 2022)
The main aim of this research is to experimentally investigate the two coupled identical ST500 gamma-type Stirling engines and convert thermal energy to cooling energy. Using a new structure and two coupled Stirling engines at different temperatures and pressures and the use of biomass fuel within the 4 -8 bar average pressure range of the first engine heat source, the 1-4 bar average pressure range of the second engine heat sink, and Stirling heat engine temperature range of 480-580 ºC, the effective cooling is obtained in the cooling engine. In doing tests, attempts were made to reach lower than 9 percent error results in different parts of the engine, including insulation, fluid leakage, belt loss, and measurement devices. According to the obtained results, 8 bars increase in the average pressure range of the gas in the first engine heat source, a 1 bar reduction in the average pressure range of the gas in the second engine heat sink, the increased temperature of the heat source up to 580ºC, and the use of the light operating fluid such as helium will affect the generation of cooling up to-16ºC.